Simuladores experimentais de radiotelescópios para o ensino de astronomia no nível médio - Araújo, Marcelo Lago (2017)
With Radio Astronomy we can study the Universe through the radio waves that reach us, taking advantage of the windows of atmospheric observation. It is an Astronomy branch that covers the development of new technologies for the capture, detection, storage and analysis of immense amounts of data. In a scenario of several technological innovations, the scientific developments from Radio Astronomy have an impact on other fields of knowledge. The study of this Science is a pertinent resource for the teaching of components of Physics, in an interdisciplinary way. Before proposing the Educational Products, with Radio Astronomy as its theme, it was necessary to experience its practical aspects, from the construction of prototypes to radioastronomical observations with experimental radio telescopes, such as Radio Jove. Field experiences have become a practice that can be adopted by other teachers. They provided knowledge for the development of the proposed Educational Products: Hertz Experiment, Adapted Galena Radio, Io-Jupiter Simulator, Pulsar Simulator, Ku Band Radio Telescope, RCFM Simulator, Teacher Workshop and Website, repository of Educational Product guides. They also collaborated on the developed methodology that includes the proposal of classroom application with the use of Conceptual Maps and V Diagrams, for diagnosis, evaluation and conduction of the experiments. The products were tested and evaluated qualitatively, from their application in events of scientific dissemination in formal and non-formal teaching environments. In these evaluations, they obtained a positive qualification that indicates their relevance to the promotion of meaningful learning, based on the items analyzed